Mount Mary Basilica designed in the Neo-Gothic style - Mumbai Archive Project Team (Jio Institute, 2024)
Mount Mary Basilica is designed in the neo-gothic style, which gained popularity in the late 19th century CE. Materials for its construction were transported by sea and carried up the hill using bullock carts and donkeys. The basilica is the fourth structure on the site. The first chapel, dedicated to Our Lady of the Mount, was established in 1570, at a time when Bandra was under Portuguese rule.